Study of the Relationship Between Blood Group and Group A Beta -Hemolytic Streptococci Isolated from Patients with Tonsillitis - Al-Ani, Rana Talib (Iraqi Journal of Science, 2022)
The aim of this study is the relationship between blood group and group A Beta-Hemolytic Streptococci, Ninety patients with tonsillitis were included in this Study from both genders and different age group for blood group study. They were attended at Ramadi Teaching Hospital during the period extended from January 2011 to June 2011. Their ages range from 3-35years.The control group included 20apparently healthy persons, while patient divided into, chronic and recurrent acute tonsillitis. Diagnostic tools were Bacteriological methods (Bacitracin method to identify and count Streptococcus pyogenes group A beta hemolytic streptococci (GABHS ).Results of blood grouping showed a reduced frequency of blood group AB- with tonsillitis and increased frequency of blood group O + with tonsillitis.